Codesign of a Quality Improvement Tool for Adults With Prolonged Critical Illness: A Modified Delphi Consensus Study - Laura Allum, MRes; Natalie Pattison, PhD; Bronwen Connolly, PhD; Chloe Apps, MSc; Katherine Cowan, MA; Emily Flowers, MRes; Nicholas Hart, PhD; Louise Rose, PhD (Critical Care Explorations, 2024)
OBJECTIVES:. Increasing numbers of patients experience a prolonged stay in intensive care. Yet existing quality improvement (QI) tools used to improve safety and standardize care are not designed for their specific needs. This may result in missed opportunities for care and contribute to worse outcomes. Following an experience-based codesign process, our objective was to build consensus on the most important actionable processes of care for inclusion in a QI tool for adults with prolonged critical illness. DESIGN:. Items were identified from a previous systematic review and interviews with former patients, their care partners, and clinicians. Two rounds of an online modified Delphi survey were undertaken, and participants were asked to rate each item from 1 to 9 in terms of importance for effective care; where 1–3 was not important, 4–6 was important but not critical, and 7–9 was critically important for inclusion in the QI tool. A final consensus meeting was then moderated by an independent facilitator to further discuss and prioritize items. SETTING:. Carried out in the United Kingdom. PATIENTS/SUBJECTS:. Former patients who experienced a stay of over 7 days in intensive care, their family members and ICU staff. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. We recruited 116 participants: 63 healthcare professionals (54%), 45 patients (39%), and eight relatives (7%), to Delphi round 1, and retained 91 (78%) in round 2. Of the 39 items initially identified, 32 were voted “critically important” for inclusion in the QI tool by more than 70% of Delphi participants. These were prioritized further in a consensus meeting with 15 ICU clinicians, four former patients and one family member, and the final QI tool contains 25 items, including promoting patient and family involvement in decisions, providing continuity of care, and structured ventilator weaning and rehabilitation. CONCLUSIONS:. Using experience-based codesign and rigorous consensus-building methods we identified important content for a QI tool for adults with prolonged critical illness. Work is underway to understand tool acceptability and optimum implementation strategies.